Comparison of vortioxetine and sertraline for treatment of major depressive disorder in elderly patients: A double‐blind randomized trial. - Borhannejad, Firouzeh; Shariati, Behnam; Naderi, Sina; Shalbafan, Mohammadreza; Mortezaei, Amirhosein; Sahebolzamani, Erfan; Saeb, Atefe; Hosein Mortazavi, Seyyed; Kamalzadeh, Leila; Aqamolaei, Ali; Ali Noorbala, Ahmad; Namazi‐Shabestari, Alireza; et al. (Journal of Clinical Pharmacy & Therapeutics, 2020)
What is known and objective: Major depressive disorder (MDD) is a complex disease and one of the leading contributors to disease burden throughout the world. In the current study, we explored the efficacy and tolerability of vortioxetine versus sertraline on symptoms of depression in elderly patients with MDD. Methods: Sixty patients diagnosed with MDD (based on DSM‐5) and Hamilton Depression Rating Scale (HAM‐D) score ≥ 19 were entered into a randomized double‐blind study and were randomized to receive either vortioxetine (15 mg daily) or sertraline (75 mg daily) for six weeks. Patients were assessed using the HAM‐D scale at baseline and weeks 3 and 6. Changes in HAM‐D score, response rates, remission rate and time to response or remission were also compared between the two study groups. Results and Discussion: Fifty patients completed the trial after six weeks. General linear model repeated measures demonstrated no difference in trend of the two treatment groups (P =.897). There was no significantly different improvement in the HDRS scores from baseline to weeks 3 and 6, as well. Differences in response rate, remission rate, time to response and time to remission periods were not statistically significant. Finally, there was not any significantly difference between the two study groups in the frequency of adverse events. What is new and conclusion: This study showed no significant differences in the efficacy and safety of vortioxetine in comparison with sertraline in order for it to be used safely for treatment of major depressive disorder in elderly patients.